La mirada del otro. La construcción de la identidad nacional, los estereotipos y la imagen de lo vasco : del enigma a la complejidad - Benjamín Tejerina; Joseba García Martín (Amnis)
The stereotype of the Basque in modern times has rested on an idyllic vision and interpretation of a remote and, to a large extent, unknown past. The narrative about Basque culture has turned the ignorance of the origins into a singularity, a differential exceptionality. Most of the cases we know involve historical facts and events, combined with diverse interpretations and fabulations to give rise to stories that narrate a persistent identity that social discourses tend to essentialize. On the question of the Basque there is no single story, but in recent times it has been monopolized by Basque nationalism. In its evolution we highlight three moments: 1) the mythification of the natural nobility of the Basque; 2) the people that fight against change, resisting and remaining faithful to their roots, 3) and, more recently, the emergence of an image of the Basque more complex, which delves into the internal contradictions and conflicts characteristic of a plural society.